1998
DOI: 10.1002/(sici)1096-9063(199802)52:2<189::aid-ps714>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Acaricide resistance management of leprosis mite (Brevipalpus phoenicis) in Brazilian citrus

Abstract: IntroductionThe Brazilian citrus industry is responsible for more than 30% of world citrus production.1 In order to compete in a global market, new production technologies are constantly reviewed and adopted by citrus producers. At the moment, among major problems that a †ect citrus production in Brazil, the phytophagous mite Brevipalpus phoenicis (Geijskes) is one of the most serious pests because it transmits citrus leprosis virus.2h4 Symptoms of the leprosis disease appear on fruits, leaves and stems and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
13

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
1
9
0
13
Order By: Relevance
“…7 There are reports that there is a northward movement of the virus, which could endanger citrus crop fields of North America. 8 Currently B. phoenicis suffers a selective pressure caused by the most commonly used acaricides on citrus crop protection such as dicofol, 9,10 hexythiazox, 11 and propargite. 12 In addition to this pressure, B. phoenicis shows parthenogenetic development leading to a quick promotion of the appearance of an evolved and chemical-resistant type of mite.…”
Section: Introductionsupporting
confidence: 84%
“…7 There are reports that there is a northward movement of the virus, which could endanger citrus crop fields of North America. 8 Currently B. phoenicis suffers a selective pressure caused by the most commonly used acaricides on citrus crop protection such as dicofol, 9,10 hexythiazox, 11 and propargite. 12 In addition to this pressure, B. phoenicis shows parthenogenetic development leading to a quick promotion of the appearance of an evolved and chemical-resistant type of mite.…”
Section: Introductionsupporting
confidence: 84%
“…It has a worldwide distribution in the tropics and subtropics (Kennedy 1995;Childers et al 2003), it is extremely polyphagous, being reported from 486 plant species from 114 different plant families (Childers et al 2003), and it rapidly develops pesticide resistance (Omoto 1998;Campos and Omoto 2002).…”
Section: Introductionmentioning
confidence: 99%
“…O controle de B. phoenicis tem sido realizado principalmente mediante o uso de produtos químicos (Omoto 1998). Devido à alta pressão de seleção, casos de desenvolvimento da resistência de B. phoenicis já foram detectados para os principais acaricidas utilizados na citricultura, tais como dicofol (Omoto et al 2000), hexitiazox (Campos & Omoto 2002) e propargite (Franco 2002).…”
unclassified